A new tool for creating personal and social EQ-5D-5L value sets, including valuing 'dead'. (February 2020) - Sullivan, Trudy; Hansen, Paul; Ombler, Franz; Derrett, Sarah; Devlin, Nancy
Abstract: The EuroQol Group's health descriptive systems, the EQ-5D-3L and its successor introduced in 2009, the EQ-5D-5L, are widely used worldwide for valuing health-related quality of life for cost-utility analysis and patient-reported health outcome measures. A new online tool for creating personal and social EQ-5D-5L value sets was recently developed and trialled in New Zealand (NZ). The tool, which includes extensive checks of the quality of participants' data, implements the PAPRIKA method – a novel type of adaptive discrete choice experiment in the present context – and a binary search algorithm to identify any health states worse than dead. After development and testing, the tool was distributed in an online survey in February and March 2018 to a representative sample of NZ adults (N = 5112), whose personal value sets were created. The tool's extensive data quality checks resulted in a 'high-quality' sub-sample of 2468 participants whose personal value sets were, in effect, averaged to create a social value set for NZ. These results overall as well as feedback from participants indicates that the new valuation tool is feasible and acceptable to participants, enabling valuation data to be relatively easily and cheaply collected. The tool could also be used in other countries, tested against other methods for creating EQ-5D-5L value sets, applied in personalised medicine and adapted to create value sets for other health descriptive systems. Highlights: A novel type of adaptive discrete choice experiment is used to value health states. Health states worse than dead are identified using a binary search algorithm. Personal value sets are produced and averaged to create a social value set. The tool enables valuation data to be relatively easily and cheaply collected. The tool could be applied in personalised medicine and to create other value sets.